Algorithmic solutions to common problems encountered during chronic total occlusion angioplasty: The algorithms within the algorithm. Issue 2 (23rd November 2018) - Riley, Robert F.; Walsh, Simon J.; Kirtane, Ajay J.; Michael Wyman, R.; Nicholson, William J.; Azzalini, Lorenzo; Spratt, James C.; Kalra, Sanjog; Hanratty, Colm G.; Pershad, Ashish; DeMartini, Tony; Karmpaliotis, Dimitri; et al.
Abstract: Improved technical equipment, dissemination of best practices, and the importance of complete coronary revascularization have led to a renewed interest in coronary chronic total occlusion (CTO) PCI. In particular, the hybrid algorithm has been associated with increasing procedural success rates in the US. However, the hybrid algorithm only covers overarching strategies in the overall approach to these lesions. Several technical challenges can occur during execution of these approaches, each of which has several potential solutions. A systematic or algorithmic approach to dealing with these challenges could contribute to improved procedural efficiency and higher procedural success. While there have been isolated attempts in the past to codify approaches to each of these situations, there has not been a contemporary, comprehensive review of the potential solutions to these problems. We present 10 common problems encountered during CTO PCI and a consensus hierarchical approach to them.